Respiratory failure patient with lung cancer diagnosed by transesophageal bronchoscopic ultrasound‐guided aspirates. Issue 4 (28th February 2018) - Ito, Takayasu; Oki, Masahide; Saka, Hideo; Kondoh, Yasuhiro; Kimura, Tomoki; Kataoka, Kensuke
Abstract : We herein report patient with respiratory failure, whose mediastinal lymph node could not be diagnosed by endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) under non‐invasive positive pressure ventilation (NPPV) but was successfully diagnosed by endoscopic ultrasound with bronchoscope‐guided fine‐needle aspiration (EUS‐B‐FNA). Abstract : A 71‐year‐old man, who had received long‐term oxygen therapy for respiratory failure caused by chronic obstructive pulmonary disease, had an enlarged mediastinal lymph node for one year. As his lung function was poor, we tried performing endobronchial ultrasound‐guided transbronchial needle aspiration under non‐invasive positive pressure ventilation for diagnosis but could not obtain sufficient specimens. Later, we performed an endoscopic ultrasound with bronchoscope‐guided fine‐needle aspiration (EUS‐B‐FNA) using a transesophageal approach. Rapid on‐site cytology revealed that adequate specimens were obtained, and we could terminate the procedure in 12 min without any complications. The histological findings revealed lung adenocarcinoma. EUS‐B‐FNA, which can be performed by a pulmonologist, is a useful alternative for diagnosing mediastinal lesions in patients with respiratory failure.